The Gatekeeping of iNews.id about News on Worship in Mosques Due to the Covid-19 Pandemic - Shania Shaufa; Thalitha Sacharissa Rosyidiani (2021)
This article explains about online media iNews.id in implementing gatekeeping function. This study aims to find out how gatekeeping efforts iNews.id in the production process on the issue of preaching restrictions on worship in mosques during Ramadan in 2020. During the Covid-19 pandemic, the current media situation, especially in the midst of a crisis, encourages the public to become heavily dependent on media coverage. With a qualitative approach, researchers analyzed five levels of influence on the gatekeeping process in online media iNews.id. The results of this study show that factors that influence the way iNews.id in the production process of preaching restrictions on worship in mosques due to the Covid-19 pandemic are the individual level of media workers, the level of media routine, the organizational level, the extramedia level, and the social system level. The conclusions of this study state the most dominant levels is the organization level and the media routine level in the iNews.id.